PENGARUH MODEL SAVI (SOMATIC, AUDITORY, VISUALIZATION, INTELLECTUALY) BERORIENTASI PERMAINAN KOTAK POS TERHADAP MOTIVASI BELAJAR SISWA - I Putu Suardipa (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2023)
This study aims to determine: the significant effect of the SAVI model oriented towards the post box game on the learning motivation of class IV Pancasila education. This study uses a quasi-experimental research type. In this study, the population was 110 students, the sample size was 38 students, which was further divided into two, there were 19 students in the experimental class and 19 students in the normal class. Based on the hypothesis that has been tested, the data assessment uses a paired sample t-test, showing the number of respondents for the experimental class is Based on the results of data analysis using an independent t-test, it is known that the tcount = 7.881 with df = 36 at a significant level of 5%, the ttable value is 1.688. From the results of these calculations it is known that tcount> ttable is 4.603> 1.688 and the value of Sig. (2-tailed) < 0.05 (0.001 < 0.05), this indicates that there is a significant difference in effect between students who take part in the SAVI Learning Model oriented towards the Post Box Game in class IV SD Negeri 3 Tamblang and students who take part in the learning with the Conventional Learning Model in class IV SD Negeri 5 Tamblang. In this case, it shows a significant difference in the influence of learning motivation between students who study with the SAVI Learning Model oriented towards the Post Box Game and the Conventional Learning Model for class IV Cluster V, Kubutambahan District.